What makes a lipase a valuable acyltransferase in water abundant medium?. Issue 12 (18th May 2017) - Subileau, M.; Jan, A. H.; Drone, J.; Rutyna, C.; Perrier, V.; Dubreucq, E.
Abstract : The necessity to develop more eco-friendly processes in oleochemistry has recently led to a renewed consideration of lipases exhibiting high acyltransferase activity in hydrated media. Abstract : The necessity to develop more eco-friendly processes in oleochemistry has recently led to a renewed consideration of lipases exhibiting high acyltransferase activity in hydrated media. Yet, what precisely differentiates a "usual" lipase from a lipase/acyltransferase and why and when the latter can be truly interesting for biocatalysis processes still need to be clearly stated. Here we propose an extensive kinetic characterization of 13 lipases including the well-known lipases A and B from Moesziomyces antarcticus ( Candida antarctica ) and lipases/acyltransferases homologous to CpLIP2 from Candida parapsilosis . The enzymes were tested in a model reaction medium comprising a fatty acid alkyl ester substrate, an alcohol as a nucleophile in a wide range of concentrations (0.01–12 M) and water at very high thermodynamic activity ( a W > 0.9). These reaction conditions allowed a clear characterization of the behavior of the different biocatalysts. Principally, lipases/acyltransferases catalyze acyl transfer at a much higher rate than hydrolysis, with fast accumulation of the fatty acid alkyl ester product up to a transient maximum concentration higher than that of the thermodynamic equilibrium, through a kinetically controlled reaction. Experimental determination of particular parameters and kinetic constants led to a classification of the lipases according to their high, average or low acyltransferase character. This study thus proposes a clear definition and a simple methodology to assess the potential of lipases for efficient fatty acid ester synthesis in aqueous media.